INNV-23. CASE REPORT OF CISPLATIN + ETOPOSIDE FOR THE TREATMENT OF METASTATIC MALIGNANT MENINGIOMA. (12th November 2021) - Nguyen, Minhdan; Truong, Judy; Sharma, Akanksha; Kesari, Santosh; Carrillo, Jose; Chow, Jared; Landa, Eve; Griffiths, Chester; Kelly, Daniel; Wagle, Naveed
Abstract: INTRODUCTION: Meningioma have an annual incidence of 5 per 100, 000 and is the most frequent primary tumor of the central nervous system. Risk factors include radiotherapy and hormone intake. Most meningioma are grade I benign tumors, but up to 15% are atypical and 2% anaplastic according to the WHO 2016 histological criteria. Extra-CNS metastasis is exceedingly rare but carry a poor prognosis. Surgical resection and radiation therapy are the only approved therapies for the treatment of high grade or recurrent meningioma. Chemotherapy options have been limited and none have shown significant response rates. METHODS: We report a case of a 33 year old male with an anaplastic meningioma (WHO Grade III) with metastasis to the lungs and rapid progression despite repeat resection. The subject was previously treated with resection and radiation therapy to a skull base/sinonasal lesion. Progression occurred at anterior cranial fossa, which required repeat resection. Within a month, the meningioma showed substantial progression with invasion into the orbit and nasopharynx as well as metastasis to the lung. The subject experienced significant clinical decline which included bilateral vision loss. The subject was treated with Cisplatin and Etoposide for 4 cycles. RESULTS: The patient had immediate clinical improvement after the first cycle. Repeat MRI imaging of the brain showed partial response with approximately 40% tumor reduction, and CT of the chest showed complete response. The subject's performance status also improved significantly with treatment including recovery of eyesight bilaterally. CONCLUSION: This case showed that the use of Cisplatin + Etoposide for metastatic malignant meningioma can have significant objective and clinical response. The use of this regimen warrants further investigation. A clinical trial is currently being developed.